Energy Transfer by Mechanical Alloying and Electrocatalytic Performance of the As-Sintered Self-Supported High-Entropy Alloy Fenicocumo - Paez-Collio, M; Paez-Collio, M; Pavez-Irrazabal, J; Pavez-Irrazabal, J; Jimenez-Arevalo, V; Jimenez-Arevalo, V (John Wiley and Sons Inc, 2025)
Efficient, stable, and cost-effective electrocatalysts for the oxygen evolution reaction (OER) are essential for clean energy generation through water splitting. This study presents a FeNiCoCuMo high-entropy alloy (HEA) synthesized via mechanical alloying (MA) and sintering using hot-pressing. The energy transfer from the milling process influences phase transformations, with the High-Entropy Alloys Prediction Software (HEAPS) predicting the formation of an FCC phase. X-ray diffraction (XRD) and scanning electron microscopy reveal an FCC phase after 150 h of milling, with no elemental segregation observed. The Burgio kinetic model estimates 448 kJ mol−1 is needed to achieve a 99% FCC phase. The crystallite size is 4 nm, with a lattice parameter of 0.371 nm. The as-milled phases were preserved during hot-pressing sintering. Electrodes (M1, M2, M3) fabricated from the HEA demonstrated high electrocatalytic efficiency, with an average overpotential of 380 mV and Tafel slope of 77 mV dec−1. At a current density of 10 mA cm−2, the electrodes maintained operation for up to 100 h. The synergy between constituent elements is key to the superior electrocatalytic performance of FeNiCoCuMo HEAs, demonstrating their potential as promising materials for OER electrocatalysis. © 2024 Wiley-VCH GmbH.